Injury and Illness Incidence in 2017 Super Rugby Tournament: A Surveillance Study on a Single South African Team - Kim Buchholtz; Curt Barnes; Theresa L. Burgess (North American Sports Medicine Institute, 2022)
# Background Professional rugby presents significant injury and illness risks to players, which need to be regularly assessed to monitor the effects of interventions and competition rules changes. # Hypothesis/Purpose The purpose of this study was to determine the incidence and nature of time-loss injuries and illness during the pre-season and competition period of the 2017 Super Rugby tournament in a single South African team. # Study Design Descriptive Epidemiology Study # Methods Forty-five adult players were recruited from one 2017 Super Rugby South African team, with 39 included in the final data set. Daily injury and illness data were routinely collected during the season by support staff over a 28-week period (January to July 2017), based on standardized injury and illness definitions. Retrospective analyses of the data were performed. # Results The incidence of match injuries (241.0 per 1000 player hours) was significantly higher than training injuries (3.3 per 1000 player hours). Twenty one percent of all injuries occurred during the tackle; 37.5% of all injuries were of a "moderate" severity. The proportion of players who sustained a time-loss injury was 76.9% (n=30). The overall incidence of illness was 1.8 per 1000 player days. Acute respiratory tract infection (28.6%) was the most common diagnosis, and the majority of illnesses (64.3%) did not result in time-loss. # Conclusion This study presented a longer study period than previous research by including the pre-season training, but represented only one single team. The incidence of match injuries was significantly higher than previously reported in Super Rugby tournaments, whereas illness rates were significantly lower. Support staff in professional rugby need to be trained on the standardized Orchard System of Classifications to ensure good quality data that can be compared to other teams within the same or other sporting codes. # Level of evidence Level 3